2023
DOI: 10.3390/su15032179
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Promotional Effect and Mechanism of Innovative City Pilot Policy on City Brand Development

Abstract: This study used Staggered DID on the panel data of 254 prefecture-level cities in China from 2005 to 2016 to explore the promotion effect and mechanism of innovative city pilot policy on urban brand development. The research shows that compared with cities without the pilot policy, the construction of innovative cities can increase the city brand value by 10% and has significantly promoted eastern, non-central cities with large populations and higher levels of science and education. Innovative city pilot polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Secondly, findings on the environmental effect of the NICP policy show that it can significantly improve energy productivity [22], green total factor energy efficiency [23], carbon emission efficiency [24], carbon emission intensity [25], and carbon lock-in [26,27]. Thirdly, findings on the innovation effect of the NICP policy show that it is conducive to promoting the flow of knowledge between industry, academia, and research institutions [28,29], city brand [30], green innovation efficiency [31], and green technology progress [32]. In contrast to the government's direct intervention in innovation through resource allocation, several studies suggest that the government should act as a coordinator or facilitator to promote innovation, and its policy formulation should focus on creating a favorable environment for innovation [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, findings on the environmental effect of the NICP policy show that it can significantly improve energy productivity [22], green total factor energy efficiency [23], carbon emission efficiency [24], carbon emission intensity [25], and carbon lock-in [26,27]. Thirdly, findings on the innovation effect of the NICP policy show that it is conducive to promoting the flow of knowledge between industry, academia, and research institutions [28,29], city brand [30], green innovation efficiency [31], and green technology progress [32]. In contrast to the government's direct intervention in innovation through resource allocation, several studies suggest that the government should act as a coordinator or facilitator to promote innovation, and its policy formulation should focus on creating a favorable environment for innovation [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the pilot policy has had a positive impact on many other aspects of urban development, including city brand development [8], financial development [9], etc. In summary, the existing studies are generally positive about the policy effects of innovative city pilots.…”
Section: Literature Review 21 the National Innovative City Pilot Policymentioning
confidence: 99%
“…On the other hand, some studies focus on urban planning itself, which includes five categories, namely the environmental planning system, the field of ideology and policy making, the field of planning in general, the field of implementation, and social feedback (Bonakdar & Audirac, 2020;Mohammadi Aydoghmish & Rafieian, 2022). In addition, other studies focus on analyzing the impact of city pilot promotions and policies in developing city brands (Yuan et al, 2023), where it was found that in cities that implement innovative city pilot policies, the development of city brands increases by 10% higher than cities without city pilot policies. This case encourages further studies on how city and regional branding relates to a sustainable environment, especially in Indonesia.…”
Section: Introductionmentioning
confidence: 99%